Egypt Water Use and Management Project - Richardson, E. V., author; Quenomoen, M. Eugene, author; Wahby, Hassan, author; Egypt Water Use and Management Project, publisher (Colorado State University. Libraries, 1982)
Egypt--fertile land and gift of the Nile. Yet today's Egypt faces a future in which the country's agricultural production cannot keep pace with its rapidly growing population. In a joint effort to solve this problem, the Government of Egypt and the United States Agency for International Development have joined together to form the Egyptian Water Use and Management Project (EWUP). Together, 178 Egyptians and 9 Americans strive to increase production on Egypt's small farms and to save the country's precious water. Colorado State University administers American involvement in the Project, drawing support staff from its own ranks and from the Consortium for International Development.
EWUP
January, 1982.
CER80-81EVR74.
Keywords: Irrigation -- Egypt -- Management; Rural development -- Egypt; Irrigation farming -- Egypt